Economic Burden of Heart Failure Hospitalizations in Canada: A Population-based Study - Emily E. Ellis, MPH; Hena Quereshi, MSc; Douglas C. Dover, PhD; M. Patrice Lindsay, RN, PhD; Sean Virani, MD; Anique Ducharme, MD, MSc; Nathaniel M. Hawkins, MD; Robert McKelvie, MD, PhD, FRCPC; Padma Kaul, PhD (CJC Open)
Background: Heart failure (HF) is associated with significant mortality and morbidity and accounts for substantial health care resources. We examined hospitalization costs of patients with HF in Canada (excluding patients from Quebec and the Territories) between 2010/2011 and 2018/2019 and estimated future costs to 2039/2040. Methods: We identified hospitalization records with a primary diagnosis of HF between 2010/2011 and 2018/2019. Concurrent hospitalizations were combined to identify episodes of care. Total hospitalization costs and costs per HF patient were calculated for each fiscal year of the study. All costs are presented in 2022 CAD$. Generalized linear models were used to project primary HF hospitalization episodes and costs to 2039/2040 on the basis of population projections from Statistics Canada. Results: There were 436,160 hospitalization episodes with a primary diagnosis of HF. Between 2010/2011 and 2018/2019, HF episodes increased from 43,114 to 54,743, and number of patients increased from 34,960 to 44,567, and total hospitalization costs increased from $684.3 million to $776.0 million, resulting in a cumulative cost of $6.65 billion. Between 2019/2020 and 2039/2040, there are projected to be 1.69 million HF hospitalization episodes, costing the Canadian health care system $19.5 billion. Conclusions: HF places a substantial economic burden on the Canadian health care system, which is likely to increase in the coming decades. Health system planning and policy solutions to identify, and reduce barriers to, HF therapies that are effective in preventing hospitalizations; and improved access to community-based services are needed to mitigate future costs. Résumé: Contexte: L’insuffisance cardiaque (IC) est associée à une mortalité et à une morbidité importantes et représente une part substantielle des ressources de santé. Nous avons examiné les coûts d’hospitalisation des patients atteints d’IC au Canada (à l’exclusion des patients du Québec et des Territoires) entre 2010-2011 et 2018-2019 et procédé à l’estimation des coûts projetés jusqu’en 2039-2040. Méthodologie: Nous avons recherché les dossiers de patients hospitalisés ayant reçu un diagnostic principal d’IC entre 2010-2011 et 2018-2019. Les hospitalisations concurrentes ont été combinées de façon à isoler les épisodes de soins. Le coût total des hospitalisations et les coûts par patient atteint d’IC ont été calculés pour chaque exercice financier au cours de l’étude. Les coûts totaux sont présentés en dollars canadiens de 2022. Un modèle linéaire généralisé (MLG) a été utilisé pour projeter le nombre et le coût des hospitalisations liées à un diagnostic principal d’IC jusqu’en 2039/2040 sur la base des projections démographiques de Statistique Canada. Résultats: Durant cette période, on a enregistré 436 160 hospitalisations liées à un diagnostic principal d’IC. Entre 2010-2011 et 2018-2019, le nombre de ces hospitalisations est passé de 43 114 à 54 743, et le nombre de patients a augmenté de 34 960 à 44 567; le coût total des hospitalisations est passé de 684,3 à 776,0 millions de dollars, entraînant des coûts cumulatifs de 6,65 milliards de dollars. Entre 2019-2020 et 2039-2040, on estime à 1,69 million le nombre d’hospitalisations liées à l’IC, selon les projections, ce qui représente des coûts de 19,5 milliards de dollars pour le système de santé canadien. Conclusions: L’IC impose un lourd fardeau économique au système de santé canadien, et il est probable que ce fardeau s’alourdira au cours des décennies à venir. Pour atténuer ces coûts à l’avenir, une planification du système de santé et des initiatives politiques visant à repérer et à contrer les obstacles au traitement de l’IC, et l’amélioration de l’accès à des services communautaires, seront nécessaires afin de prévenir ces hospitalisations.